2011
DOI: 10.1055/s-0030-1256324
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal obstruction due to a collapsed biodegradable esophageal stent

Abstract: A 74-year-old man with a previous history of surgery for pharyngolaryngeal neoplasia and reconstruction in 2006 with muscle graft was referred to our unit for dysphagia. Upper endoscopy showed a narrow stricture at the muscle graftesophageal anastomosis that was 20 mm long. The patient underwent five sessions of esophageal dilation with the CRE Balloon Dilator (Boston Scientific, Natick, Massachusetts, USA) with early relapse and weight loss. Therapeutic options were discussed with the patient, and we decided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Reported complications of biodegradable stents include retrosternal pain and stent migration. However, there are some recent reports of biodegradable oesophageal stents eroding into the tracheobronchial tree causing airway compromise [ 5 ], severe tissue reaction with hyperplastic in- and overgrowth causing stent obstruction [ 3 ] and even oesophageal obstruction due to their collapse [ 3 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reported complications of biodegradable stents include retrosternal pain and stent migration. However, there are some recent reports of biodegradable oesophageal stents eroding into the tracheobronchial tree causing airway compromise [ 5 ], severe tissue reaction with hyperplastic in- and overgrowth causing stent obstruction [ 3 ] and even oesophageal obstruction due to their collapse [ 3 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that the stent degraded and collapsed after 9 weeks. The collapsed mesh did not allow the passage of a standard Pentax endoscope [41]. To overcome these issues of poor corrosion resistance and a quick loss of mechanical support of BD stents, Yuan et al mixed biodegradable poly( ε -caprolactone) (PCL) and poly(trimethylene carbonate) (PTMC) as the coated membrane to coat magnesium alloy stents for a fully biodegradable esophageal stent.…”
Section: Self-expandable Stentsmentioning
confidence: 99%
“…Other potential rare complications of BDS that have been addressed are biodegradable esophageal stents eroding into the tracheobronchial tree causing airway compromise [100], collapse of the biodegradable stent mesh inside the esophageal lumen [57,101], tracheoesophageal fistula [59] and a feeling of obstruction because food stuck in the BDS one months later [81].…”
Section: Complications Of Biodegradable Esophageal Stentsmentioning
confidence: 99%